Muzeum sztuki - miejsce wizualizacji nowoczesności - Popczyk, Maria (Przestrzenie Teorii, 2009)
Art museum is a space of visualisation of myths and narration of modernity, combines in itself rationality with emotionality, thus provides ambivalent experiences to the audience. Critics of museums such as D. Preziosi present the negative side of the Enlightenment rationality: objectification of artworks and of the subject, building of scientific constructions acting for authorities. In turn, theoreticians who are favorably disposed towards museums such as O. Marquard or A. Huyssen convince that the museum in modern times performs a compensatory role, and its postmodern form allows a magnitude of histories and aesthetics. However, it was ultimately J.-F. Lyotard who becomes its patron, since artist choosing museum for their activities resist the established thought, realising Lyotard's idea of justice as a dispute.